Wild Radish (Raphanus raphanistrum L.) Is a Potential Reservoir Host of Cucurbit Chlorotic Yellows Virus - Saritha R. Kavalappara; David G. Riley; Paulo S. G. Cremonez; Jermaine D. Perier; Sudeep Bag (Viruses, 2022)
Cucurbit chlorotic yellows virus (CCYV) belongs to the genus Crinivirus and is part of a complex of whitefly-transmitted viruses that cause yellowing disease in cucurbits. In the southeastern USA, heavy incidences of CCYV have been observed on all cucurbits grown in the fall. CCYV was detected from wild radish (Raphanus raphanistrum L.), a common weed that grows in the southeastern USA by high-throughput sequencing as well as RT-PCR. CCYV sequence from wild radish was 99.90% and 99.95%, identical to RNA 1 and RNA 2 of cucurbit isolates of CCYV from the region. Transmission assays using whiteflies demonstrated that wild radish is a good host for CCYV. Whiteflies were also able to acquire CCYV from wild radish and transmit the virus to cucurbit hosts, which developed typical symptoms associated with CCYV. Using quantitative PCR, the titer of CCYV in wild radish was also estimated to be on par with that of cucurbit hosts of the virus. Whitefly bioassays revealed that wild radish is an acceptable feeding and reproductive host plant. These results indicate that wild radish could serve as a reservoir host for CCYV in the USA and other parts of the world where similar conditions exist.